AN ORIGINAL COPY: THE FILM ADAPTATION OF KAZUO ISHIGURO’S NEVER LET ME GO / ORJİNAL BİR KOPYA: KAZUO ISHIGURO’NUN NEVER LET ME GO ROMANININ FİLM UYARLAMASI - Hatice YURTTAŞ (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
This article compares Kazuo Ishiguro’s Never Let Me Go and Mark Romanek’s film adaptation of the text with the same title. Discussing the novel’s deconstructive strategies through which the categories of the human, authenticity and copy are unsettled, it is suggested that Ishiguro’s text distinguishes itself from science fiction genre where these categories are affirmed by relocating them in a hierarchical relationship. Ishiguro reveals the power of fiction and stories in constructing identity based on dualities and this applies to both the clone and the human. The film, on the other hand, is a reassuring science fiction where the human is offered as a determined category by setting the identity of the human against its other- nonhuman or clone.